Synergies between biodiversity conservation and sustainable rural development of adjacent communities: a case study of the Tsitsikamma National Park - Faasen, Helena (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MScConsEcol (Conservation Ecology and Entomology)--University of Stellenbosch, 2006.